PENGEMBANGAN MEDIA WORDWALL BERBASIS NEARPOD MATERI SEL UNTUK MENINGKATKAN HASIL BELAJAR SMPN 12 PEMATANGSIANTAR - Nurul Fadila; Mastiur Verawaty Silalahi; Gunaria Siagian (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The role of technology in learning in schools is very important and diverse. Learning media that are not varied makes students bored in following the learning, so the learning objectives cannot be conveyed properly to students. Through interview data and observations of researchers through science teachers at SMP Negeri 12 Pematangsiantar, data from the results of the mid-term exams of students were obtained that 43.2% of students completed while 56.8% of students did not complete so from this data it was found that many students did not complete science learning. The purpose of this study was to determine the effect of using wordwall game learning media based on the nearpod application and to determine students' responses to wordwall game learning media based on the nearpod application. The researcher used (Research and Development (R&D) as the type of research and used the ADDIE model. The results of the feasibility test of the nearpod application-based wordwall game media based on 4 feasibility tests by expert validators obtained an overall percentage of 81.6% very feasible. The achievement of students in classes that use nearpod application-based wordwall game teaching materials has a high value compared to those who do not use nearpod application-based wordwall game media. The student response to the nearpod application-based wordwall game media as a learning medium obtained a percentage of 83.3%% with a good category.  Keywords: Learning Media, Wordwall Game, Nearpod Abstrak: Peran terknologi dalam pembelajaran di sekolah sangat penting dan beragam. Media pembelajaran yang tidak bervariasi membuat siswa menjadi jenuh dalam mengikuti pembelajaran, maka tujuan pembelajaranya tidak dapat tersampaikan dengan baik kepada siswa. Melalui data wawancara serta pengamatan peneliti melalugu pendidik IPA di SMP Negeri 12 Pematangsiantar diperoleh data hasil UTS siswa bahwasanya siswa yang tuntas 43,2% sedangkan siswa yang tidak tuntas sebanyak 56,8% jadi dari data ini didapatkan banyak siswa yang tidak tuntas pada pembelajaran IPA. Adapun tujuan dari penelitian ini adalah untuk mengetahui pengaruh penggunaan media pembelajaran game wordwall berbasis apliksi nearpod serta mengetahui respon siswa terhadap media pembelajaran game wordwall berbasis apliksi nearpod. Peneliti memakai (Research and Development (R&D) sebagai jenis penelitiannya serta memakai model ADDIE. Hasil uji kelayakan media game wordwall berbasis aplikasi nearpod berdasarkan 4 uji kelayakan oleh para validator ahli memperoleh hasil persentase keseluruhan 81,6% sangat layak. Pencapaian peserta didik di kelas yang memakai bahan ajar game wordwall berbasis apliksi nearpod memiliki nilai yang tinggi dibandingkan yang tidak memakai media game wordwall berbasis apliksi nearpod. Adapun tangapan siswa terhadap media game wordwall berbasis apliksi nearpod sebagai media pembelajaran diperoleh persentase 83,3%% dengan kategori baik. Kata Kunci: Media Pembelajaran, Game Wordwall, Nearpod